Alternative Histories of the Self : A Cultural History of Sexuality and Secrets, 1762-1917 - Clark, Anna (2017)
An exploration of how the idea of the unique self was rejected and reformulated by individuals in 18th- and 19th-century Western Europe, often to justify gender and sexual transgression.